Harmony of Pancasila Values and the Principle of Religious Moderation in Criminal Law Reform in Indonesia - Iqbal Kamalludin; Bunga Desyana Pratami; Achmad Jauhari Umar; Itsna Muna Yanuar (Badan Pembinaan Ideologi Pancasila, 2025)
This study examines the alignment between Pancasila values and religious moderation in Indonesia's criminal law reform. The old Criminal Code, inherited from the colonial era, has been criticized for its lack of social justice and religious freedom. The key problem addressed is how the new Criminal Code can embody Pancasila values while preventing religious radicalism and extremism. Observations focus on articles in the old code that are seen as unresponsive to human rights and plurality. A juridical-normative approach is employed, analyzing the new Criminal Code's relationship with Pancasila and religious moderation principles. The analysis includes primary legal documents, such as the new Criminal Code, and relevant secondary literature. Philosophical, historical, and normative methods are used to develop legal logic aligned with Pancasila, aiming to solve the problem of religious intolerance. The results indicate that the new Criminal Code introduces significant reforms to protect religious freedom, focusing on preventing radicalism and enhancing rehabilitative sanctions. These reforms represent a major step towards a more inclusive and just legal system. The conclusion drawn is that the new Criminal Code is expected to harmonize criminal law with Pancasila values and religious moderation, providing more humanistic and preventive approaches to religious issues. This research contributes by offering a new perspective on criminal law reform that emphasizes national values and presents a legal model more suited to Indonesia’s diverse society.